1972
DOI: 10.1063/1.1677168
|View full text |Cite
|
Sign up to set email alerts
|

Tracer Diffusion and Shear Viscosity for the System 2,6-Lutidine-Water near the Lower Critical Point

Abstract: Tracer diffusion coefficients of tritiated water in mixtures of 2,6-lutidine-water have been measured over the entire concentration range at E=1.1XlO-4 below the critical point using the diaphragm cell. No anomaly was detected. The shear viscosity coefficients were measured across the entire concentration range at E=2.246XlO-2 , 1.268 X 10-2 , 7.8XlO-5 by a closed capillary viscometer. The observed anomaly in the region of the critical point was further characterized by studying the temperature dependence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 21 publications
6
20
0
Order By: Relevance
“…[32]. In Table IV, we list our dynamic viscosity values measured along the isotherm at 25.00"C. From the figure and the table, it is evident that our data are in good agreement with those of Stein et a/.…”
Section: Viscositysupporting
confidence: 90%
See 2 more Smart Citations
“…[32]. In Table IV, we list our dynamic viscosity values measured along the isotherm at 25.00"C. From the figure and the table, it is evident that our data are in good agreement with those of Stein et a/.…”
Section: Viscositysupporting
confidence: 90%
“…Below, we report interdiffusion data for 2,6-lutidine + water along the critical isopleth and along isotherms at 25.00"C and 33.00"C. Complete specification of the cross-over function, however, requires also information concerning the viscosity of the mixture [ 18,201. Viscosity data taken along the critical isopleth and isotherms at 26.969"C, 29.969"C, and 33339°C have been collected by Stein et al [32]. We have confirmed their results for the critical isopleth and report here in addition a Tew observations take along the isotherm at 25.00"C. We have also found that the data of Stein et al [32] can be readily extrapolated to match our own at 25.00"C.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The lack of data for the latter system at higher temperatures results from the miscibility gap above 307 K at mole fractions of the amine x 2 range from 0.007 to 0.44 [14]. The results for the mixtures of 2,6-dimethylpyridine with water are close to the viscosities reported by Stein et al [15].…”
Section: Resultssupporting
confidence: 75%
“…With this two component theoretical model for particle diffusion behavior in critical mixtures, we are able, not only to expalin our light scattering results, but also to reconcile these with the results of tracer diffusion studies in critical mixtures [3] and the microphotography results of a Russian group [4].…”
mentioning
confidence: 65%